HIDEA syndrome: A new case report highlighting similarities with ROHHAD syndrome - Harvengt, J.; Lumaka, A.; Fasquelle, C.; Caberg, J. H.; Mastouri, M.; Janssen, A.; Palmeira, L.; Bours, V. (Frontiers in Genetics, 2023)
Context: ROHHAD syndrome presents a significant resemblance to HIDEA syndrome. The latter is caused by biallelic loss-of-function variants in the P4HTM gene and encompasses hypotonia, intellectual disabilities, eye abnormalities, hypoventilation, and dysautonomia. We report the first patient identified with HIDEA syndrome from our ROHHAD cohort. Clinical case: Our patient was a 21-month-old girl who had a history of severe respiratory infections requiring intensive care, hypotonia, abnormal eye movements, and rapid weight gain. Polysomnography identified severe central hypoventilation. During her follow-up, a significant psychomotor delay and the absence of language were gradually observed. The prolactin levels were initially increased. Hypothermia was reported at 4 years. Exome sequencing identified a new homozygous truncating P4HTM variant. Discussion: Our patient met the diagnosis criteria for ROHHAD, which included rapid weight gain, central hypoventilation appearing after 1.5 years of age, hyperprolactinemia suggesting hypothalamic dysfunction, and autonomic dysfunction manifesting as strabismus and hypothermia. However, she also presented with severe neurodevelopmental delay, which is not a classic feature of ROHHAD syndrome. HIDEA syndrome presents similarities with ROHHAD, including hypoventilation, obesity, and dysautonomia. To date, only 14% of endocrinological disturbances have been reported in HIDEA patients. Better delineation of both syndromes is required to investigate the eventual involvement of P4HTM, a regulator of calcium dynamics and gliotransmission, in ROHHAD patients. Conclusion: In the case of clinical evidence of ROHHAD in a child with abnormal neurological development or eye abnormalities, we suggest that the P4HTM gene be systematically interrogated in addition to the analysis of the PHOX2B gene. A better delineation of the natural history of HIDEA is required to allow further comparisons between features of HIDEA and ROHHAD. The clinical similarities could potentially orient some molecular hypotheses in the field of ROHHAD research.